Autism Spectrum Disorder and Diet - Michelle A. Zitt; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS)
There are thousands of Internet sites about ASD and diet, but much of the information has no scientific proof. If you are considering making changes to your child's diet, the information in this 4-page fact sheet will help you to understand the potential risks and benefits of these changes. Written by Michelle A. Zitt, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.